Extremely low frequency magnetic fields emitted by cell phones - Misek, J.; Jakus, J.; Hamza Sladicekova, K.; Zastko, L.; Veternik, M.; Jakusova, V.; Belyaev, I. (Frontiers in Physics, 2023)
Cell phones expose significant parts of the human brain and head to extremely low frequency (ELF) magnetic fields (MF) classified by the IARC as a 2B carcinogen. ELF MF was measured on the front and back sides of 15 cell phones in standby, speaking, and listening modes for 2G and 3G standards in two frequency bands, LF1: 5 Hz – 200 Hz and LF2: 120 Hz – 10 kHz. The highest MF value was 70.03 µT (RMS) in LF1 (2G, listening mode, front side) and 12.67 µT (RMS) in LF2 (2G, speaking mode, front side). The 3G cell phones consistently emitted a lower ELF MF compared to the 2G ones. The exposure to ELF MF was also simulated at various locations (head, thorax, pelvis) using the CST Studio Suite. The simulations revealed 8.45 µT, 7.5 µT and 6.09 µT in the middle of the head (midbrain), 3.89 µT, 3.98 µT and 2.83 µT for the middle of the thorax (heart), and 2.03 µT, 1.96 µT and 1.56 µT in the middle of the pelvis (scrotum) for 10 Hz, 50 Hz and 200 Hz, respectively. These values are comparable to those reported to induce biological and health effects, including those related to carcinogenesis. The results can be used in future studies concerning the ELF exposure or the combined effects of electromagnetic fields of radiofrequency and ELF.